2019
DOI: 10.3390/soilsystems3020037
|View full text |Cite
|
Sign up to set email alerts
|

Digital Mapping of Soil Classes Using Ensemble of Models in Isfahan Region, Iran

Abstract: Digital soil maps can be used to depict the ability of soil to fulfill certain functions. Digital maps offer reliable information that can be used in spatial planning programs. Several broad types of data mining approaches through Digital Soil Mapping (DSM) have been tested. The usual approach is to select a model that produces the best validation statistics. However, instead of choosing the best model, it is possible to combine all models realizing their strengths and weaknesses. We applied seven different te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…More recently, advanced techniques have been used; including, exponential decay functions [14], polynomials [15], or equal-area splines [16]. One of the most popularly applied are splines which have been used to model continuous changes of soil properties with depth [11,[17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, advanced techniques have been used; including, exponential decay functions [14], polynomials [15], or equal-area splines [16]. One of the most popularly applied are splines which have been used to model continuous changes of soil properties with depth [11,[17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an ensemble model is at least as strong as the prediction of any of the primary model. High potential of MA methods in digitally modelling soil texture (Caubet et al, 2019; Román Dobarco et al, 2017), soil taxonomic classes (Taghizadeh‐Mehrjardi et al, 2019), and soil organic carbon (Chen et al, 2020) has also been reported. However, previous studies showed high potential of MA, the best‐performing algorithm may vary between study areas and for different soil properties, and thus optimization of MA methods is case‐specific (Chen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A novel ensemble approach was used here to spatially combine predictions from the five most precise prediction models. Although ensemble methods have been widely used in other disciplines [45,47,73,74] this method has not previously been used to predict Site Index. Most ensemble approaches combine predictions from all models across the entire study area using a range of approaches to weight the individual model predictions [73,75].…”
Section: Discussionmentioning
confidence: 99%
“…As each modelling method has its own limitations and advantages [44] an alternative approach for improving the overall model precision is to combine predictions from each model [45,46]. This method, which is known as Ensemble Modelling, is a well known methodology that can improve prediction through integrating knowledge from many sources [46].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation